Analysis of Women’s Economic Empowerment and Domestic Violence Prevention Policy Implementation based on Gender Transformative (GT) Approach in North Aceh Regency - Aruni, Fidhia; Safrida, Safrida; Safrida, Nila; Bahri, Saiful; Kurniawan, Rudi (Jurnal Borneo Administrator, 2025)
Domestic violence remains a serious problem in Indonesia, especially in North Aceh, which has the second highest number of domestic violence cases in Aceh. This research analyzes the North Aceh District Government's economic empowerment policy implementation in tackling domestic violence using the GenderTransformative (GT) approach. Using a phenomenological qualitative method, this research conducted in-depth interviews with various parties, including the Department of Social Affairs, Women's Empowerment and Child Protection, and analysis of related documents. The results showed that despite the existence of Aceh Qanun (Local Law) No. 9 of 2019 and North Aceh Regent Regulation No. 9 of 2022 that regulate women's empowerment and handling of domestic violence, implementation still faces many challenges. The main obstacles are weak interagency coordination, lack of community and NGO participation, and limitedunderstanding of the relevant qanuns. More integrated and effective local, mesomacro, and inter-organizational interventions must be strengthened. In conclusion, achieving gender equality and reducing domestic violence through economic empowerment requires a more comprehensive approach. The North Aceh regional government is advised to enhance coordination, increase community and NGO participation, and develop sustainable empowerment programs considering the local context and Islamic values